Evaluation of stent-graft implantations for intramural hematoma based on fluid-solid interaction analysis. (15th August 2020) - Zhang, Xuelan; Zheng, Liancun; Luo, Mingyao; Shu, Chang; Wang, Erhui
Highlights: FSI analysis (the interactions of blood, SG and arterial wall) is employed to evaluate SG surgery for IMH. Effects of SG implantation depth, deployment length, material and shape on arterial wall and stent are investigated. Von-Mises stress of IMH increases as d increases or L decreases, with remarkable variations at d  ∈ [0.2, 0.4] or L  ∈ [33.3%, 60%]. Von-Mises stressmax occurs at the junction of healthy and IMH and the discrepancy among SGs reaches 37.6%. WSS linearly increases as L, d and SG stiffness decreases. Abstract: Endovascular stent-graft (SG) repair for patients with intramural hematoma (IMH) requires suitable SG deployment to avoid complications. In this paper, several SG implantation schemes are quantitatively evaluated by CFD tool, in which the mutual interactions between blood, SG and arterial wall are taken into account. Factors considered: (i) the depth d of SG implantation into the vascular wall; (ii) the deployment length L (exceeding O % of the lesion); (iii) the material of SG; (iv) the shape of SG. The total deformation, Von-Mises stress and wall shear stress (WSS) on arterial wall and stent are analyzed, and particularly the related fitting curves are displayed. The results show that the Von-Mises stress exerted on IMH wall increases with the increment in d or decrement in L, with remarkable variations at about d  ∈ [0.2, 0.4] or L  ∈ [33.3%, 60%]. The stress for IMH wall is linear inverse correlation with SG stiffness, and the stress discrepancy among different SGs is up to 37.6%. The Von-Mises stressmax for arterial wall and stent appears at the junction of healthy and IMH walls and the region where the SG curvature changes the most, respectively. Further, although the fluctuation of WSS is smaller than that of Von-Mises stress, the WSS remains linearly increasing with the decrement of L, d and material stiffness. Results obtained can potentially serve as the guideline to SG surgery for IMH patients.